Process Modelling of the Calcium Looping Process and Validation Against 1 MWth Pilot Testing. (July 2017) - Haaf, M.; Stroh, A.; Hilz, J.; Helbig, M.; Ströhle, J.; Epple, B.
Abstract: The calcium carbonate looping (CaL) process is a promising post-combustion technology for CO2 capture from fossil-fired power plants and carbon intense industries like steel and cement manufacturing. A CaL system consists basically of two interconnected circulating fluidized bed (CFB) reactors using natural limestone as a sorbent. Inside the carbonator, CO2 contained in the flue gas is absorbed by the exothermic carbonation reaction, during endothermic sorbent regeneration in the calciner, CO2 is released consequently. The CaL technology has proven its feasibility in semi-industrial scale by pilot testing in various test rigs all over the world. For the further development of the process, models are required for the prediction of process characteristics in terms of heat and mass flows. Most critical to the calculation of an overall process performance is the CO2 absorption efficiency in the carbonator and, moreover, the decreasing CO2 carrying capacity of the sorbent during operation. The enrichment of impurities like ash or calcium sulfate in the circulating sorbent as well as the reduction in particle size due to attrition needs also to be taken into account when assessing the performance of a CaL system. The main focus of this paper is the development of an advanced steady state process model and its validation against 1 MWth long term pilot testing. The validation of the process model showed good agreement in predicting the CO2 absorption efficiency of the carbonator as well as the sorbent regeneration in calciner. Furthermore, the composition, and the effect of attrition to particle size distribution of the circulating sorbent are reproduced with good accordance. The process model is further applied for a sensitivity study to show the influence of crucial parameters on the particle size reduction as well as on the calciner efficiency.